2020
DOI: 10.1186/s12933-020-01025-4
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver index and development of cardiovascular disease in Koreans without pre-existing myocardial infarction and ischemic stroke: a large population-based study

Abstract: Background: Despite the known association between non-alcoholic fatty liver disease (NAFLD) and cardiovascular disease (CVD), whether NAFLD predicts future CVD events, especially CVD mortality, remains uncertain. We evaluated the relationship between fatty liver index (FLI), a validated marker of NAFLD, and risk of major adverse cardiac events (MACEs) in a large population-based study. Methods: We identified 3011,588 subjects in the Korean National Health Insurance System cohort without a history of CVD who un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 34 publications
8
67
1
1
Order By: Relevance
“…The presence of systemic inflammation promoted by cytokines secreted from the liver leads to endothelial dysfunction, altering vascular tone and enhancing vascular plaque formation. This mechanism was supported by a clinical study that found a significant association between the severity of NAFLD and both surrogate markers of atherosclerosis and an increased risk of cardiovascular mortality in NAFLD patients [25][26][27][28].…”
Section: Discussionmentioning
confidence: 76%
“…The presence of systemic inflammation promoted by cytokines secreted from the liver leads to endothelial dysfunction, altering vascular tone and enhancing vascular plaque formation. This mechanism was supported by a clinical study that found a significant association between the severity of NAFLD and both surrogate markers of atherosclerosis and an increased risk of cardiovascular mortality in NAFLD patients [25][26][27][28].…”
Section: Discussionmentioning
confidence: 76%
“…Notably, the strong bidirectional relationship between NAFLD and CVD is well established. Indeed, Kim et al recently showed that NAFLD has prognostic value for identifying individuals who are at higher risk for CVD [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2) opinion [27]; (3) manuscripts in Chinese and Russian languages [28,29]; (4) article evaluating the differential expression genes of NAFLD and in acute myocardial infarction datasets [30]; and (5) an article published under hepatology elsewhere section where the full article is already included in our systematic review [31]. Hence, a total of 14 records fulfilled our inclusion and exclusion criteria and were included in our qualitative assessment and systematic review as described in Figure 1 [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Literature Searchmentioning
confidence: 99%
“…Six studies had a cohort study design (retrospective cohort study [35,46], prospective cohort study [36,37], prospective population-based cohort study [41], matched cohort study [42], nationwide population-based cohort study [43], and cohort study [44,47]). Moreover, two studies had a cross-sectional study design (cross-sectional study [32] and cross-sectional analysis of a prospective single-center study [45]) and two observational studies (retrospective observational study [34,40]).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation